Neutrophil-to-albumin ratio mediates the association between Life’s Crucial 9 and chronic obstructive pulmonary disease - Feng, Jing; Gong, Hongyang (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation and chronic airway inflammation. Life’s Crucial 9 (LC9) is a comprehensive tool for evaluating cardiovascular and metabolic health. The neutrophil-to-albumin ratio (NPAR) has been proposed as a novel inflammation-nutrition biomarker. This study aimed to elucidate the association between LC9 scores and the prevalence of COPD while also assessing the potential mediating role of NPAR.MethodsA cross-sectional analysis was conducted using data from 25,634 U.S. participants in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. Multivariable logistic regression, stratified subgroup analyses, and restricted cubic spline (RCS) models were employed to evaluate the association between LC9 and COPD.ResultsAmong the 25,634 participants, 1,248 reported a history of COPD. After adjusting for multiple covariates, each 10-unit increase in the LC9 score was associated with a 28% lower odds of COPD (OR = 0.72, 95% CI: 0.67–0.77), whereas each one-unit increase in NPAR was associated with a 6% higher odds of COPD (OR = 1.06, 95% CI: 1.03–1.10). Similar trends were observed when LC9 and NPAR were categorized into different levels (P for trend < 0.05). RCS analysis revealed a linear inverse relationship between LC9 scores and COPD prevalence. Mediation analysis indicated that NPAR accounted for 4.84% of the association between LC9 and COPD (p < 0.001).ConclusionHigher LC9 scores were associated with a reduced risk of COPD, with NPAR acting as a significant mediator in this relationship. These findings highlight the potential value of optimizing cardiovascular health in COPD prevention strategies and underscore the importance of controlling inflammation and improving nutritional status. Further prospective studies are warranted to validate these preliminary findings.